Fishery and stock assessment of Fenneropenaeus indicus (H.Milne Edwards) from Kozhikode, south west coast of India. - Sarada, P T (Indian Journal of Fisheries, 2011)
<!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> The average annual catch of Fenneropenaeus indicus in the trawl landing of Puthiappa, Kozhikode was 197 t with a CPUE of 15 kg. Peak fishing period was April-May. About 28% of the average annual shrimp catch was constituted by F. indicus. The stock assessment studies indicated that the fishery is still underexploited and the effort can be increased to obtain the maximum sustainable yield.